The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1186/1471-2407-10-393
|View full text |Cite
|
Sign up to set email alerts
|

Short rare hTERT-VNTR2-2nd alleles are associated with prostate cancer susceptibility and influence gene expression

Abstract: BackgroundThe hTERT (human telomerase reverse transcriptase) gene contains five variable number tandem repeats (VNTR) and previous studies have described polymorphisms for hTERT-VNTR2-2nd. We investigated how allelic variation in hTERT-VNTR2-2nd may affect susceptibility to prostate cancer.MethodsA case-control study was performed using DNA from 421 cancer-free male controls and 329 patients with prostate cancer. In addition, to determine whether the VNTR polymorphisms have a functional consequence, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Moreover, there are also several reports indicating that minisatellite polymorphisms can influence gene expression. 16 , 17 , 24 , 25 , 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there are also several reports indicating that minisatellite polymorphisms can influence gene expression. 16 , 17 , 24 , 25 , 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Similar results for transcriptional regulation by minisatellite fragments were previously reported with H-Ras , IL-1α, IGF2 , MUC6 and TERT genes. 16 , 17 , 24 , 25 , 26 Minisatellites of IL-1α, MUC6 and TERT may control gene expression in cancer cell lines, although these are located in the intronic regions of genes. 16 , 17 We suggest that BORIS –MS2, located in the promoter region, differentially regulates the gene transcription in cancer cells and normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These VNTRs were also discussed as having an enhancer function for gene transcription. In vitro studies on PrCa cell lines analyzing the activity of the TERT promoter in combination with different VNTR variants clearly showed an increased luciferase activity for the VNTR2-2nd variants [22,23] . These effects might also be expected for TERT expression and could also increase the individual risk for PrCa.…”
Section: Discussionmentioning
confidence: 99%
“…Additional genome‐wide association studies found this region to be associated with increased risk for both pancreatic cancer and lung adenocarcinoma [99–104]. Unlike the studies involving breast cancer, an increased risk of prostate cancer was found to be associated with at least one hTERT variation that influences telomerase expression [105, 106]. Other studies have linked cancer risk and telomerase SNP for several cancers including the following: bladder cancer [106, 107], ovarian cancer [108] and cervix cancer [106].…”
Section: Tert and Terc Variations And Disease Predispositionmentioning
confidence: 99%